Multilocular Cystic Variant of Nephroblastoma in an Adult Chicken- A Case Report - Dhanush Krishna, B; Devi, S.S; Sajitha, I.S; Krithiga, K; Divya, C; Prasanna, K.S (The Indian Veterinary Journal, 2023)
Here, a case of nephroblastoma in an adult chicken is described where extensive multilocular cyst formation with limited classic triphasic growth pattern were noticed histologically.